2012
DOI: 10.1128/jvi.00675-12
|View full text |Cite
|
Sign up to set email alerts
|

Single Amino Acid Modification of Adeno-Associated Virus Capsid Changes Transduction and Humoral Immune Profiles

Abstract: Adeno-associated virus (AAV) vectors have the potential to promote long-term gene expression. Unfortunately, humoral immunity restricts patient treatment and in addition provides an obstacle to the potential option of vector readministration. In this study, we describe a comprehensive characterization of the neutralizing antibody (NAb) response to AAV type 1 (AAV1) through AAV5 both in vitro and in vivo. These results demonstrated that NAbs generated from one AAV type are unable to neutralize the transduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 68 publications
2
82
0
Order By: Relevance
“…Interestingly, this study showed that the antibody-driven alteration of receptor usage resulted in a more virulent phenotype in experimentally infected animals. In experiments using adeno-associated virus (AAV), Li and colleagues have likewise shown that small numbers of amino acid changes in the viral capsid protein can simultaneously shift cellular tropism and also promote escape from antibody-mediated neutralization in experimentally vaccinated animals (10). A recent study of porcine rotavirus also provides an example of apparent antibody escape variations clustered around the viral receptor-binding site (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this study showed that the antibody-driven alteration of receptor usage resulted in a more virulent phenotype in experimentally infected animals. In experiments using adeno-associated virus (AAV), Li and colleagues have likewise shown that small numbers of amino acid changes in the viral capsid protein can simultaneously shift cellular tropism and also promote escape from antibody-mediated neutralization in experimentally vaccinated animals (10). A recent study of porcine rotavirus also provides an example of apparent antibody escape variations clustered around the viral receptor-binding site (11).…”
Section: Discussionmentioning
confidence: 99%
“…For other viral families, mutations that drive escape from antibody-mediated neutralization are sometimes accompanied by a shift in the use of cellular receptors for infectious entry (10,11). To address this possibility, we performed an additional set of analyses examining the binding characteristics and cellular entry tropism of each of the BKV serotypes.…”
mentioning
confidence: 99%
“…On the third day of treatment, mice were transduced with the indicated dose of AAV vector in PBS by retro-orbital injection. Live imaging of luciferase expression from AAV vectors has been previously described (44). Briefly, mice were given 150 mg/kg D-luciferin (Caliper LifeSciences) by i.p.…”
Section: Methodsmentioning
confidence: 99%
“…IHC of these eyes did not reveal any major tropism differences compared to rAAV2, in that RGC, Müller glia, and other cells of the INL were transduced by the chimeric capsid. A more recent paper has shown the amino acid at position 265 on the rAAV2.5 capsid to be solely responsible (42). Therefore, we tested an rAAV2-265D mutant capsid intravitreally, which revealed expression similar to that of the rAAV2.5 parent (see Fig.…”
Section: Hs Binding Increases the Ivit Transduction Of Other Raav Sermentioning
confidence: 96%